Visitors' segmentation at Penang National Park using place attachment approach - Ibrahim, Nabila Aiza (2016)
Market segmentation is an important tool in planning effective marketing strategies and a viable tool in the planning process for minimizing the impact of visitors‘ depreciative behavior, development of effective public relations, educational programs and visitor risk management. While studies ofvisitors in many ecotourism destinationsare widely adopted travel motivation as segmentation tool, this study looks for an approach to segment visitors at ecotourism site by using place attachment. Besides that, this study is designed to differentiate segmented visitors according to their socio-demographic backgrounds, behavioral variables and travel motivations.Therefore, a survey was conducted to 387 respondents using self-administered and convenience sampling design where respondents were asked to choose and rate their agreement on items measuring place attachment (place identity and place dependent), (2) socio-demographic background, (3) behavioural variables (trip characteristics, main destinations and activity preferences) and (4) travel motivations (setting and visit motivation). K-means clustering analysis was used to cluster respondents into three groups; high attachment, medium attachment and low attachment based on their place attachment score. An accompanying F-test analysis on these three groups indicated significant differences with regard to their place identity and place dependence score. High attachment visitors scored higher mean on place identity and place dependence at (M=4.13; M=3.93) as compared to medium (M=3.20; M=2.99) and low attachment visitors (M=2.33; M=2.11) on F (2,384) = 526.2, p=.00 and F (2,384) = 514.4, p=.00. Result indicated that there were 90 respondents (23.3%) in the high attachment groups, 195 respondents (50.4%) in the medium attachment group and 102 respondents (26.3%) in low attachment groups.Furthermore, Chi-square test of independent at p<.05 with Bonferroni test was used to determine the characteristics of each of the place attachment group as according to their socio-demographic background and behavioural variables Moreover, Analysis of Variance (ANOVA) at p<.05 with Scheffe test was then used to determine the characteristics of each of the place attachment groups as according to their travel motivations. Based on the result, high attachment group was likely to be older with the range of age from 41 to 61 years old and above, academician and researcher as the main occupational background. Most of them were repeat visitors and nature viewing was their main activities. Moreover, highly attached visitors‘ main destinations at PNP were Pantai Kerachut and Teluk Kampi, most of them came to PNP alone and their source of motivation were more towards the ‗self-enrichment‘ with benefits attainment. On the other hand, medium attachment group were slightly young with the range of age from 20 to 40 years old. Most of them were homemaker/retiree/student and business/services as their occupational background. Most of the medium attached visitors were first time visitors with hiking/tracking, fishing and photography as their activities at PNP. Their main destination at PNP were Teluk Aling (USM CEMAC) and Teluk Duyung (Monkey Beach) while some can be found at Sungai Tukun.They liked to travel with their friends and their source motivation to visit PNP was to be creative and came to PNP on the account of PNP was a good place for outdoor activities. Furthermore, low attachment group was younger with the range of age below than 30 years old, and most of them were first time visitors. Their main activities were picnicking and came to PNP with their family and organization. They preferred Pasir Pandak and Sungai Tukun as their main destination and their motivation to visit PNP was to do or conduct activities with their family and group and pulled by the motivation of PNP as a good place to spend their time with family and companion. Based on the result, this study propose several implications on the ecotourism development at PNP where it enables managers, planners and policy makers to better link the profile of visitors into the ecotourism development for better future of the park. Such result can be used in the management action to minimize the impacts of park visitation, marketing ecotourism product and developing effective risk management in the park.